The Linguistics of Imaginary Narrative Spaces in Daphne du Maurier’s Rebecca - Newman, John; Ньюман, Джон (My University, 2019)
Daphne du Maurier’s 1938 novel Rebecca provides rich opportunities for the study of imaginary narrative spaces and the language associated with such spaces. The present study explores the linguistics of the imaginary narrative spaces in Rebecca, drawing upon three lines of linguistic research consistent with a Cognitive Linguistic approach: (i) an interest in understanding and appreciating ordinary readers’ actual responses (rather than merely relying upon “expert” readers’ responses), (ii) the construction of worlds or “spaces”, and (iii) the application of ideas from Cognitive Grammar. The study reveals a surprisingly intricate interplay of linguistic devices used in the construction of imaginary narrative spaces and the maintenance of such spaces in extended discourse. Роман «Ребекка» Дафни дю Мор’є 1938 року надав великі можливості для вивчення уявних наративних просторів й мовлення, яке прийнято асоціювати з ними. У цьому дослідженні увагу приділено лінгвістиці уявних наративних просторів у романі «Ребекка». Автор розглядає три лінії лінгвістичних досліджень у річищі когнітивно- лінгвістичного підходу, а саме: а) зацікавленість у розумінні та оцінці реальних відповідей читачів (замість того, щоб просто покладатися на «експертні» відповіді читачів); б) побудова світів або «просторів»; в) застосування ідей когнітивної граматики. Дослідження виявило доволі заплутану й складну взаємодію мовних засобів, які використовує автор роману для побудови уявних наративних просторів й утримання таких просторів у подальшому дискурсі.
Лінгвістика уявних наративних просторів у романі «Ребекка» Дафни дю Мор’є
Keywords: imaginary narrative space; du Maurier; cognitive linguistics; cognitive grammar; stylistics; repetition; уявний наративний простір; дю Мор’є; когнітивна лінгвістика; когнітивна граматика; стилістика, повторення